Investigating the Key Factors Influencing Falling Object Incidents at Construction Sites in Batu Pahat, Johor - Rahim, Ikhmal Iskandar; Ismail, Shafawi (Journal of Advanced Mechanical Engineering Applications, 2024)
Building construction refers to the methods and businesses associated with assembling and erecting structures, particularly those designed for residential purposes. The need for a controlled environment to mitigate the effects of climate change was initially purely functional. A construction site presents a wide range of ever-evolving threats, with risks that are often unique to the construction business. Therefore, ensuring that workers are well-trained and aware of these risks is essential for safeguarding themselves and their coworkers from potential harm or even fatalities. This research aims to explore the root causes and consequences of falling object incidents on individuals, assets, and reputation within the construction industry. Thoroughly analyzing the root causes and consequences of incidents informs the development of a targeted intervention plan. This plan aims to reduce severity and address specific issues, such as inadequate safety measures or equipment failures, with the overarching goal of significantly decreasing falling object incidents. This study employs a survey questionnaire as its methodological tool. The procedure includes conducting literature reviews and incorporating sample survey questionnaires from previous researchers. The methodology used to analyze the statistical data was SPSS software via Reliability Tests, One-way ANOVA Tests, and Correlation and Interferential Analysis. The results revealed a strong statistical correlation (r > 0.5, n = 50, p < 0.05) between organizational/departmental roles and responsibilities, the behavioral behavior of construction workers, incidents at work, health/disease problems, and the consequences of the incident. Therefore, to mitigate all the potential consequences, some intervention plans are being proposed, such as the implementation of Toolbox Meeting (TBM) and Toolbox Talk (TBT), a Toolbox Training Program, and the monitoring of physiological conditions for construction workers to maintain the well-being of the workforce and ensure a safe working environment.